RiceMoRe: Digitalizing Rice Monitoring for Climate Action and Scalable Impact - International Rice Research Institute (2025)
The Rice Activity Monitoring and Reporting System (RiceMoRe) is a digital solution co-created and implemented in Vietnam from 2018 to 2024 to address critical challenges in monitoring, reporting, and verification (MRV) of rice activities, particularly concerning greenhouse gas (GHG) emissions. Previously, Vietnam lacked a digital system for tracking progress toward emission reduction targets, relying on manual, inconsistent, and often inaccurate reporting methods. This posed significant barriers to demonstrating climate mitigation achievements and accessing climate finance. RiceMoRe overcame this by digitizing the existing government reporting line, standardizing data entry, minimizing errors, and ensuring hierarchical quality controls. Developed on open-source platforms, it provides a low-cost, flexible, and replicable system. The primary outcome is the official adoption of RiceMoRe by Vietnam’s Ministry of Agriculture and Rural Development (MARD), currently Ministry of Agriculture and Environment, scaling across approximately 75% of the country’s rice planting areas, significantly enhancing the efficiency, accuracy, transparency, traceability, and accessibility of agricultural data for climate action and sustainable rice management.